2020
DOI: 10.29350/qjps.2020.25.3.1115
|View full text |Cite
|
Sign up to set email alerts
|

Some Fixed Point Theorems in n−normed spaces

Abstract: In this article, we recall the definition of a real n-normed space and some basic properties. fixed point theorems for types of Kannan, Chatterge, Zamfirescu, -Weak contraction and  - (,)-Weak contraction mappings in  Banach spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As a result of the growing desire for improved material qualities to meet market demands, nanoparticles have been integrated into composite materials. Several studies can be found in the open literature that focused on the reinforcement of the mechanical and physical properties of composites using nanoparticles [11][12][13][14]. Some successful examples of these studies are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the growing desire for improved material qualities to meet market demands, nanoparticles have been integrated into composite materials. Several studies can be found in the open literature that focused on the reinforcement of the mechanical and physical properties of composites using nanoparticles [11][12][13][14]. Some successful examples of these studies are discussed below.…”
Section: Introductionmentioning
confidence: 99%